Speaking the language of defence: narratives of doctoral examiners on the PhD viva - Tan, Wee Chun (Emerald, 2022)
Purpose: This paper aims to investigate doctoral examiners' narratives on their expectations of the candidate's oral performance in the PhD viva. Both the PhD examiners and handbooks that offer advice on the PhD viva preparation appear to share the same expectation of the candidate's oral performance in the viva. That is, candidates must answer questions to the satisfaction of examiners to warrant a pass in the oral examination. However, what constitutes a satisfactory viva performance – let alone an excellent one – is often undefined. Design/methodology/approach: Using narrative inquiry as the guiding research approach to investigate this issue, 12 experienced doctoral examiners from across the disciplines at a Malaysian research university were interviewed. Their narratives were analysed inductively. Findings: The findings show that examiners expect candidates to speak the language of defence by manifesting confident, interactional behaviour, providing credible and convincing responses and displaying doctoralness. The aspects of candidate's oral performance undesired by the examiners, as well as the reasons for having such expectations, are also discussed. The paper argues that the expectations of examiners in the PhD viva should be made explicit and communicated to the candidates and examiners to ensure a positive doctoral assessment process and outcome. Originality/value: This paper contributes to the literature on doctoral assessment, particularly on the PhD viva, through the voices of examiners in the Global South. It also offers an examiner expectancy model of the PhD viva.